Betahistine Treatment in a Cat Model of Vestibular Pathology: Pharmacokinetic and Pharmacodynamic Approaches - Tighilet, Brahim; Léonard, Jacques; Watabe, Isabelle; Bernard-Demanze, Laurence; Lacour, Michel (Frontiers in Neurology, 2018)
This study is a pharmacokinetic and pharmacodynamic approach using betahistine doses levels in unilateral vestibular neurectomized cats (UVN) comparable to those used in humans for treating patients with Menière’s disease. The aim is to investigate for the first time oral betahistine administration (0.2 and 2 mg/kg/day) with plasma concentrations of betahistine and its major metabolite 2PAA (N=9 cats), the time course of posture recovery (N=13 cats), and the regulation of histidine decarboxylase (HDC: enzyme synthesizing histamine) in the tuberomammillary nuclei (TMN) of UVN treated animals (N= the same 13 cats plus 4 negative control cats). In addition the effect of co-administration of the lower betahistine dose (0.2 mg/kg/day) and selegiline (1 mg/kg/day), an inhibitor of the monamine oxidase B (MAOBi) implicated in betahistine catabolism was investigated. The pharmacokinetic parameters were the peak concentration (Cmax), the time when the maximum concentration is reached (Tmax) for both betahistine and 2PAA and the area under the curve (AUC). The pharmacodynamic approach consisted at quantifying the surface support area, which is a good estimation of posture recovery. The plasma concentration-time-profiles of betahistine and 2PAA in cats were characterized by early Cmax values followed by a phase of rapid decrease of plasma concentrations and a final long lasting low level of plasma concentrations. Co administration of selegiline and betahistine increased values of Cmax and AUC up to 146- and 180-fold, respectively. The lowest dose of betahistine (0.2 mg/kg) has no effects on postural function recovery but induced an acute symptomatic effect characterized by a fast balance improvement (4-6 days). The higher dose (2 mg/kg) and the co-administration treatment induced both this acute effect plus a significant acceleration of the recovery process. The histaminergic activity of the neurons in the TMN was significantly increased under treatment with the 2mg/kg betahistine daily dose, but not with the lower dose alone or in combination with selegiline. The results show for the first time that faster balance recovery in UVN treated cats is accompanied with high plasma concentrations of betahistine and 2PAA, and upregulation of HDC immunopositive neurons in the TMN. The higher betahistine dose gives results similar to